Pengaruh Pola Duduk di Kelas Terhadap Prestasi Akademik Siswa Sekolah Dasar - Rahmi Gusni Herman; Puti Michelle Maryam; Paris Naofel Ramadhan; Sartono Sartono (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
The arrangement of seating patterns in the classroom is one of the learning environment factors that can affect student comfort, concentration, achievement and interaction during the learning process. This study aims to determine how the influence of seating patterns in the classroom on the academic achievement of elementary school students. The method used is qualitative with data collection techniques of observation, interviews and documentation. In the interview stage, an interview was conducted with one of the teachers at SDIT Permata Kita, observation was carried out in a participatory manner, and documentation in the form of student seating patterns in the classroom, recapitulation of student grades and documentation with the teacher. The results showed that seating patterns affect classroom dynamics, student participation, and student-teacher interaction during the learning process.